Canais de comercialização de orgânicos: desafios e alternativas de agricultores familiares do leste paulista - Oliveira, Priscila Silveira de (2014)
This paper aims to describe some market alternatives adopted by smallholders farmers on the distribution channels for organic in natura products. Therefore, besides the literature review on this matter, the methodology includes the collection of primary data based on semi-structured interviews with fourteen smallholders farmers. The interviewees are smallholders farmers from eastern side of Sao Paulo, geographically located between two river basins: Capivari-Piracicaba basin and Mogi Guacu. Farmers are found by snow ball method. It is showed that the distribution channels, so called short channels , are the mainly strategies used on family farming. The market fairs are the sell places which the farmers chose as the best one for their needs. The main reasons for that are the better prices they can get due to the absence of any middleman in the selling process and the closest approach to the consumers. The worst channel in their opinions is the supermarkets due to unfavorable contracts required. Those contracts include lower prices, assuming the products that were over (not sold) and bonus profits to the supermarkets on special occasion to name some of them. This study showed that is important to implement actions to enable organic agriculture and commercialization management, logistics and accounting in the distribution process of these products. Considering this, formal or informal associations for production or commercialization have showed to be more efficient and safe compared to individual work, especially as a strategy for production diversification, constancy in offer and searching for new markets.